Deduction and Geography in Conan Doyle’s A Study in Scarlet - Andréas Pichler (Cahiers Victoriens et Edouardiens)
At first sight, detective fiction and geography appear as two opposing fields of study. Geography relies on tangible scientific information while detective novels create mysteries around whodunnits, notably with Doyle’s Sherlock Holmes adventures. Detective Holmes reasons backwards, relying on his ‘theory of deduction’, a fictional method of using pertinent facts to unravel murder mysteries usually committed in dubious circumstances. Holmes’s method, however, stems from concrete geographical details. The purpose of looking at both ‘sciences’ in Doyle’s A Study in Scarlet is to facilitate the study of facts and fiction, from which emerges a juxtaposition in which character depiction and narration are dialectically intertwined. Reading together the art of fiction and the science of geography thus becomes a critical necessity. Looking at both indeed enables us to grasp more fully how character depiction and narrative structure operate in Doyle’s detective stories.